Transformation of Beauueria bassiana strain Bb9112 with the genes from the green tluorescent protein and the protease prlA of Metarhizium anisopliae - GÓNGORA-B., CARMENZA E. (Revista Colombiana de Entomología, 2004)
In order to produce an improved strain of the entomopathogen Beauveria bassiana, fungus transformation system was developed based on resistance to the herbicide glufosinate ammonium, conferred by the bar gene. B. bassiana strain Bb 9112, characterized by its resistance to UV light, was transformed with the plasmid pBarGPE l , previously cloned with the marker gene coding for green fluorescent protein (GFP). Transformed colonies were selected in a minimal medium containing 25 ¡,g/ml of the herbicide glucosinate ammonium. The expression of the protein GFP in the transformed protoplasts and the mycelium regenerated from those protoplasts was confirmed by UV light microscopy. Pathogenicity tests indicated no significant differences in percent pathogenicity between the transformed and non• transformed strains. In order to increase the pathogenicity of Bb9112 against the coffee berry borer, it was transformed with the plasmid pBarGPEl-prlA containing a subtilisin protease gene (prlA) isolated from Metarhizium anisopliae. In the transgenic strain the presence of the prlA gene was identified by PCR. The expression of the protein was confirmed by isoelectrofocus and enzymatic activity.